From Policy To Culture: The Role of Principals in Institutionalizing Ecological Catechesis in Catholic Senior High Schools - Manfred Habur, Agustinus (Ridwan Institute, 2026)
This study examines the role of Catholic school principals in sustaining ecological catechesis programs in Catholic senior high schools in the Diocese of Ruteng, Eastern Indonesia. While ecological catechesis has increasingly been promoted within Catholic education, its long-term sustainability often depends on institutional leadership rather than individual teacher initiatives. Using a qualitative intrinsic case study design, the research draws on semi-structured interviews, participant observation, and document analysis to explore how principals support ecological catechesis through school policies, leadership practices, and cultural institutionalization. The findings reveal that principals contribute to program sustainability by articulating an ecological vision grounded in Catholic social teaching, translating it into formal regulations and budget priorities, and fostering ecological practices as part of school culture. However, structural constraints such as limited resources, competing academic demands, and socio-economic pressures continue to challenge institutional consistency. This study highlights the underexplored pastoral-ecological leadership of Catholic principals and offers contextual insights for strengthening ecological education in faith-based schools.